FAKTOR-FAKTOR SOSIAL EKONOMI YANG MEMPENGARUHI KUANTITAS PADI YANG DIJUAL PETANI DI KECAMATAN IMOGIRI KABUPATEN BANTUL - S Nuryanti; Mochammad Maksum; Masyhuri Masyhuri (Agro Ekonomi, 2001)
The aim of this research is to know socioeconomic factors that influence paddy quantity sold by farmer when floor price policy for paddy grain and rice were implemented. Farmer respondents have been chosen in the development area of paddy in Imogiri Subdistrict of Bantul Regency as representative respondents.Cobb Douglas Production Function is transformed to natural logarithm to analyze model of paddy quantity sold by farmer function. Estimation method was run using ordinary least square of multiple regression analysis to know significant level of each socioeconomic factor variable to paddy quantity sold by farmer variable.This research shows that paddy quantity sold by farmer is influenced by such factors, paddy price, price of urea fertilizer, quantity of urea fertilizer, farmer's need of cash money, member and composition of farmer, irrigation quality, as well as land cultivation method